Biocatalytic Dearomatisation Reactions - Gerlach, Tabea; Turner, Nicholas J. (Synthesis, 2024)
Biocatalytic dearomatisation offers the advantages of high chemo-, regio- and stereoselectivity over chemical strategies. Mono- and dioxygenases with dearomatising properties are already well-established tools for the synthesis of natural products and beyond. Herein, we review investigations of protein sequence–activity relationships, as well as protein-engineering approaches that have been employed to expand the substrate scope of biocatalysts and achieve product regio- and stereodiversity. Thus, oxidative dearomatising biocatalysts offer an increasingly diverse toolbox for the synthesis of asymmetric, oxidised cyclic scaffolds, as illustrated through selected examples of biocatalytic applications in synthetic routes towards natural products and derivatives thereof. Reductases with dearomatising properties have been less well investigated, so we review recent mechanistic findings which, henceforth, allow for expanding applications of this class of biocatalysts. Additionally, chemoenzymatic strategies have been developed to overcome the limitations of purely biocatalytic or chemical dearomatisation approaches. We highlight examples of those combination strategies for the synthesis of asymmetric privileged motifs.1 Introduction2 Oxidative Biocatalytic Dearomatisation3 Reductive Biocatalytic Dearomatisation4 Chemoenzymatic Dearomatisation5 Conclusion
Keywords: biocatalysis; dearomatisation; enzymes; protein engineering; oxidative